Molecular Characterization of Carbapenemase-Producing Enterobacterales in Children with Diarrhea in Rural Burkina Faso - Dembélé, René; Soulama, Issiaka; Kaboré, Wendpoulomdé Aimé Désiré; Konaté, Ali; Kagambèga, Assèta; N'Golo, David Coulibaly; Traoré, Oumar; Seck, Abdoulaye; Traoré, Alfred Sababenedyo; Guessennd, Nathalie; Gassama-Sow, Amy; Barro, Nicolas (Journal of Drug Delivery and Therapeutics, 2021)
Background and objective: In recent years, carbapenemase-producing Enterobacterales (CPE) resistance to antibiotics has dramatically increased leading to limitations of their treatment options. In the present study, we investigated the occurrence of carbapenemase-producing Escherichia coli and Salmonella in rural Burkina Faso. Materials and methods: Salmonella isolates were serotyped according to the Kauffman White scheme. Diarrheagenic Escherichia coli (DEC) strains was identified using 16-plex Polymerase Chain Reaction (PCR), whereas antibiotic susceptibility was realized using the disk diffusion method. Furthermore, multiplex PCR assays were carried out using oligonucleotides to detect the presence of genes of the blaKPC, blaVIM, blaIMP, blaTEM, blaSHV, blaOXA and blaCTX-M types in all E. coli and Salmonella strains. Results: The study highlighted high resistance rates of the identified bacteria to common antibiotics. Likewise, two strains of E. coli were imipenem resistant with carbapenemase-encoding genes. The genes detected were Klebsiella pneumoniae carbapenemase (KPC), Verona integrin-encoded metallo-β-lactamase (VIM) and Imipenemase (IMP-2) reaching a rate of 40% each in E. coli strains. However, no Salmonella carbapenemases blaKPC, blaVIM or blaIMP were detected. Conclusion: This study showed that for a real-time infection control and prompt application of antimicrobial chemotherapy, characterization of carbapenemase-producing Enterobacterales in patients is crucial. Keywords: Antibiotics, Carbapenemase-Producing Enterobacterales, children, Burkina Faso